Cognitive frailty as a predictor of dementia among older adults: A systematic review and meta-analysis. (March 2020) - Zheng, Lufang; Li, Guichen; Gao, Dawei; Wang, Shuo; Meng, Xiangfei; Wang, Cong; Yuan, Haibo; Chen, Li
Highlights: Cognitive frailty is a significant predictor of incident dementia. It is much possible that the predictive validity on dementia is stronger than that of either frailty or cognitive impairment alone. Health caregivers can identify and intervene cognitive frailty as soon as possible, which possesses a potential benefit of preventing or delaying dementia. Abstract: Objective: The aim of this systematic review and meta-analysis was to synthesize the pooled risk effect and to determine whether cognitive frailty is a predictor of dementia among older adults. Design: Systematic review and meta-analysis. Setting and participants: PubMed, EMBASE, Web of Science, and the Cochrane Library were systematically searched until June 5, 2019. Only cohort studies and population-based longitudinal studies published in English were eligible. Study selection, data extraction and quality assessment of including studies were independently completed by two researchers. A fixed-effects model was used to synthesize the risk of baseline cognitive frailty on dementia in the older adults compared with older adults without cognitive frailty. Measurements: The risk of cognitive frailty on incident dementia. Results: Of the 1566 identified records, 7 studies met the inclusion criteria and were included in the review. And 4 studies reporting hazard ratio (HR) of incident dementia for cognitive frailty were included in the meta-analysis. Synthesized results showed that baseline cognitive frailty in the elderly was significantly associated with an increased risk of developing dementia as compared with those without cognitive frailty (prefrailty + CI model: pooled HR = 3.99, 95 %CI = 2.94–5.43, p < 0.00001, I 2  = 31 %; frailty + CI model: pooled HR = 5.58, 95 %CI = 3.17–9.85, p < 0.00001, I 2  = 0 %). Heterogeneity across the studies was low. Conclusion: Cognitive frailty is a significant predictor of dementia. Cognitive frailty status may be a novel modifiable target in identification of early signs before dementia.